Conceptualising and testing the emerging regional power' of Turkey in the shifting nternational order - PARLAR DAL, EMEL (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2016)
Turkey has thus far been generally neglected in most IR studies on power categorisations, such as middle or middle-range power, regional power or rising/emerging power, despite its rising regional power status in the past decade. This paper attempts to understand Turkey's regional power together with its rising power status using an integral approach. In doing so, it empirically tests whether or not Turkey fits Daniel Flemes's regional power' category, which seems to be proposing a more complete and integral framework through the fulfilment of four basic preconditions: claim to leadership; possession of necessary power resources (material and ideational); employment of material, institutional and discursive foreign policy instruments; and acceptance of leadership by third parties. Based upon these analytical tools, the article will discuss Turkey's performance in creating a regional impact in its neighbouring regions of the Middle East, the Balkans and the Black Sea and Caucasus.
Keywords: Regional power; rising power; emerging regional power; Turkish foreign policy; foreign policy instruments; power resources; BRICS; FOREIGN-POLICY; MIDDLE-EAST; HEGEMONY; IRAQ